Scaling with households: socially inclusive locally led scaling of climate adaptation practices in dairy systems of Kenya - DuttaGupta, Tanaya; Bullock, Renee; Habermann, Birgit; Gichuki, Leah; Kiptoo, Emmaculate (CGIAR System Organization, 2024)
Locally led adaptation occurs in communities where gender inequalities exist. Knowledge networks as scaling mechanisms are socially differentiated and access to knowledge, and distribution of labor and income are uneven. Lack of attention to understanding how gender and innovations interact will reinforce inequitable relations. Scaling with households is an approach that works with multiple household members to integrate gender into an existing Livestock, Climate and Systems Resilience innovation focusing on dairy systems in Nandi and Bomet counties, Kenya. Participatory approaches are used to co-develop and plan with dairy households such as farmer-led field days that reflect gender specific demand. Sex disaggregated group discussions in workshop have shed early insights about how to improve the approach. Women co-leading roles, sharing with their networks, and scheduling adjustments were recommended to support inclusive participation. Involving women from dairy households to lead field day activities would support socially inclusive scaling of farmer-to-farmer knowledge networks.